2005
DOI: 10.1185/030079905x38141
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum tumor necrosis factor alpha and ferritin may contribute to the insulin resistance found in HCV positive Egyptian patients

Abstract: Patients with HCV infection had a significantly higher level of TNFalpha and ferritin which may explain their insulin resistance. HOMA index and serum TNFalpha levels correlated positively with the HCV load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…However, in their study, these levels correlated to the degree of alanine transaminase elevation as a marker of hepatic injury, which does not agree with our results. In partial agreement with our results were those of El-Sammak et al, 14 in 2005, who reported significantly higher levels of TNF in patients with HCV infection HCV and those with HCV infection and diabetes compared with patients with diabetes alone and control subjects, without any significant difference between patients with HCV infection and those with HCV infection and diabetes. El-Zayadi et al 15 had demonstrated a significant difference between HCV-infected individuals and healthy blood donors within the Egyptian groups.…”
Section: Discussionsupporting
confidence: 94%
“…However, in their study, these levels correlated to the degree of alanine transaminase elevation as a marker of hepatic injury, which does not agree with our results. In partial agreement with our results were those of El-Sammak et al, 14 in 2005, who reported significantly higher levels of TNF in patients with HCV infection HCV and those with HCV infection and diabetes compared with patients with diabetes alone and control subjects, without any significant difference between patients with HCV infection and those with HCV infection and diabetes. El-Zayadi et al 15 had demonstrated a significant difference between HCV-infected individuals and healthy blood donors within the Egyptian groups.…”
Section: Discussionsupporting
confidence: 94%
“…Elsammak et al 25 have demonstrated increased levels of serum TNF-α in 27 Egyptian patients with HCV infection, which showed significant positive correlation with the HCV RNA viral load. In addition, Talaat 26 has reported elevation of TNF-α levels in 82 patients with HCV infection (20 patients with mild cirrhosis, 20 patients with moderate cirrhosis, 20 patients with severe cirrhosis, and 22 patients with hepatocellular carcinoma) at different stages of disease.…”
Section: Discussionmentioning
confidence: 97%
“…Most importantly, we report the novel finding that C10 is effective at blocking palmitate and LPS-induced activation of IL6 and iNos-producing inflammatory pathways in both 3T3L1 adipocytes and RAW 264.7 macrophages without blocking insulin-stimulated AKT signaling, suggesting that C10 may be efficacious as a novel therapeutic agent for the treatment of obesity/inflammation-induced insulin resistance. Furthermore, since C10 inhibits LPS and palmitate induction of iNos expression in both adipocytes and macrophages, it might also be beneficial in correcting the stress-induced hyperglycemia observed in acute inflammatory processes such as infection/sepsis (Berstein 2005, De Souza et al 2005, Elsammak et al 2005. It is clear, however, that additional studies into the effects of C10 on FFA-induced insulin resistance (i.e.…”
Section: Discussionmentioning
confidence: 99%